Rare earth element (REE) in surface mangrove sediment by instrumental neutron activation analysis - Kumar, Krishnan; Saion, Elias; Mohamed Kamari, Halimah; Yap, Chee Kong; Hamzah, Muhd Suhaimi (Springer Netherlands, 2014)
A study is carried out on the concentrations of rare earth element (REE) elements present in surface mangrove sediments from 10 locations throughout west coast Malaysia. In carrying out the analysis, the best and most convenient method being the instrumental neutron activation analysis (INAA). Samples were obtained, dried, crushed to powdery form and samples prepared for INAA. All the samples for analysis were weighted approximately 150 mg for short irradiation and 200 mg for long irradiation time. As calibration and quality control procedures, blank samples, standard reference material SL-1 were then irradiated with thermal neutron flux of 4 × 1012 cm−2 s−1 at the MINT TRIGA Mark II research reactor which operated at 750 kW by using a pneumatic transport facility. The REE elements of surface sediment samples in this study are Dy, Sm, Eu,Yb, Lu, Tb, La and Ce. It was found that the level of concentrations of all the REE elements varies in the range (0.35–117.4 mg/kg). The geochemical behavior of REEs in surface sediments and normalized pattern (chondrite and shale) has been studied. The degree of sediments contaminations were computed using an enrichment factor. The results showed that the enrichment factor varied in the range (0.75–6.75).